In vitro antioxidant activities of extract and oil from roselle (Hibiscus sabdariffa L.) seed against sunflower oil autoxidation - Nyam, Kar Lin; Teh, Y. N.; Tan, Chin Ping; Long, Kamariah (Nutrition Society of Malaysia, 2012)
Introduction: In order to overcome the stability problems of oils and fats,synthetic antioxidants such as butylated hydroxyanisole (BHA), butylated hydroxytoluene (BHT) and tert-butyl hydroquinone (TBHQ) have widespread use as food additives in many countries. Recent reports reveal that these compounds may be implicated in many health risks, including cancer and carcinogenesis. Hence, there is a move towards the use of natural antioxidants of plant origin to replace these synthetic antioxidants. Methods: In this study, roselle seed oil (RSO) and extract (RSE) were mixed with sunflower oil, respectively to monitor degradation rate and investigate antioxidant activity during accelerated storage. Results: The antioxidant activity was found to stabilise sunflower oil of various samples and in the order of RSE>RSO>tocopherol>sunflower oil. The total percentage increased after 5 days of storage period in free fatty acid (FFA), peroxide value (PV) and anisidine value (AV). Total oxidation value (TOx) of sunflower oil supplemented with 1500 ppm RSE was 33.3%, 47.7%, 14.5%, and 45.5%, respectively. While the total percentage increased under different analysis methods, sunflower oil supplemented with 5% RSO was 17.2%, 60.4%, 36.2% and 59.0% in the order of FFA, PV, AV and TOTOX. Both RSO and RSE were found to be more effective in stabilisation of sunflower oil compared to tocopherol. Total phenolic content of RSE was 46.40 ± 1.51 mg GAE/100g of oil while RSO was 12.51 ± 0.15 mg GAE/100g of oil. Conclusion: The data indicates that roselle seed oil and seed extract are rich in phenolics and antioxidant activities and may be a potential source of natural antioxidants.